Externally-induced shear waves in the right ventricular free wall throughout the cardiac cycle. (4th February 2022) - Wei, L; Alipour Symakani, R; Caenen, A; Keijzer, LBH; Merkus, D; Bartelds, B; Taverne, Y; Van Der Steen, AFW; Vos, HJ; Strachinaru, M
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): 1. NWO STW/Dutch Heart foundation 2. NWO Vidi TTW Background: The right ventricular (RV) size and function have prognostic value, not only in right heart conditions (pulmonary hypertension, congenital heart disease), but also in left ventricular (LV) disease states. There is currently no noninvasive method for measuring the elastic properties of the RV walls. Increased RV diastolic stiffness however, as determined invasively, is linked to adverse prognosis in pulmonary arterial hypertension. In the LV, new high frame rate (HFR) echocardiography applications have been used in order to determine the propagation speed of naturally-occurring or externally-induced shear waves (SW) in the septum, which is related to myocardial stiffness. Purpose: We show for the first time that SWs in the RV free wall (RVFW) can be externally induced and imaged transthoracically with ultrasound. Methods: SW imaging was performed using a linear array with a programmable research ultrasound system, aimed at the parasternal long-axis view of a 5-weeks-old Yorkshire-Landrace pig (Fig. 1a). SWs were induced by a high intensity focused beam (f0 = 4.5 MHz) on the RVFW (Fig. 1a). This push beam generates a downwards force at the focus, which induces SWs that propagate left and right from the focus along the RVFW, visible on tissue Doppler images (TDI) shown in Figure 1b-c. SW propagation was imaged (f0 = 5.2 MHz) using HFR ultrasound (Fig. 1b, frame rate = 3 kHz). Three acquisitions of 1 second were performed, where 14 SWs were sequentially induced during each acquisition. ECG signal was captured simultaneously and synchronized offline. SW speeds were estimated using a custom, semi-automatic pipeline that includes TDI calculation, and SW speed estimation along a manually traced spline on the RVFW. This was repeated two times to include variability due to the manual processes. Up to four SW speed estimates were made after each push beam. SW speed estimation was repeated for all push pulses throughout the cardiac cycle, and the mean and standard deviation of the estimates were plotted (Fig. 2). Results: At least 85% of the waves were tracked successfully for all acquisitions. Diastole and systole were identified using the ECG signal (Fig. 2a). The average SW speed was 0.6 ± 0.1 m/s at end-diastole (Fig. 2b). The measured speeds ranged from 0.5 ± 0.1 m/s during diastole to 1.9 ± 0.3 m/s during systole. The changes in SW speeds correspond to the expected variation in muscle stiffness during the heart cycle as the RV relaxes and contracts. Conclusions: We demonstrate for the first time the induction and tracking of shear waves in the RVFW of a closed-chest pig. The possibility to noninvasively quantify RV wall stiffness opens a large field of translational research, with direct applications in pulmonary hypertension, congenital heart disease and heart failure in general. Pathological increase in stiffness should be further investigated in longitudinal case/control studies.